Ministers for Foreign Affairs of Ukrainian Soviet Socialistic Republic (1944–1991): Historical and biographical analysis - Якубець А. (Видавничо-поліграфічний центр "Київський університет", 2016)
The article is the attempt of the personal and resumptive analysis of persons and activity of leaders of Ministry of Foreign Affairs of Ukrainian Soviet Socialistic Republic in 1940–1980th. In particular, a social origin, geography of birth places, education (higher educational establishments), basic stages of life of ministers, reason and circumstance of their arrival to the MFA and retirements from office, personal and professional qualities are illustrated. The process of integration of Soviet Ukraine in international structures (UN, UNESCO, ILO, IAEA etc.) as basic possible direction of activity of republican MFA in the conditions of Soviet Union is described. Comparing to the analogical structure of Byelorussian SSR is realized. About, mainly, decorative character of Foreign Ministry of Soviet Ukraine in relation to independence of international contacts infer. At the same time, the positive of presence of own MFA regarding to training of personnel in the field of foreign policy is marked. The last circumstance, in turn, allowed Ukraine to enter into independence with the already formed professional diplomatic corps.

Стаття є спробою персонального та узагальнюючого аналізу осіб та діяльності керівників міністерства закордонних справ Української Радянської Соціалістичної Республіки у 1940–1980-х рр. Зокрема, висвітлюється соціальне походження, географія місць народження, освіта (вищі навчальні заклади), основні етапи життєвого шляху міністрів, причини та обставини їхнього приходу до МЗС та відставок з посади, особисті та професійні якості. Охарактеризовано процес інтеграції УРСР у міжнародні структури (ООН, ЮНЕСКО, МОТ, МАГАТЕ та ін.) як основний допустимий в умовах Радянського Союзу напрям діяльності республіканського МЗС. Здійснено порівняння із аналогічною структурою Білоруської РСР. Зроблено висновок про, здебільшого, декоративний характер зовнішньополітичного відомства УРСР щодо самостійності міжнародних контактів. Водночас, відзначено позитив наявності власного МЗС стосовно виховання кадрів у сфері зовнішньої політики. Останнє, в свою чергу, дозволило Україні вступити у незалежність із уже сформованим професійним дипломатичним корпусом.
Міністри закордонних справ УРСР (1944–1991 рр.): історико-біографічний аналіз
Keywords: Ministry of Foreign Affairs of Ukrainian Soviet Socialistic Republic; A. Baranovskyi; D. Bilokolos; A. Zlenko; O. Korniichuk; V. Kravets; D. Manuilskyi; V. Martynenko; L. Palamarchuk; H. Shevel; Міністерство закордонних справ УРСР; А. Барановський; Д. Білоколос; А. Зленко; О. Корнійчук; В. Кравець; Д. Мануїльський; В. Мартиненко; Л. Паламарчук; Г. Шевель